Analysis of PH3 spectra in the Octad range 2733–3660 cm−1. (December 2017) - Nikitin, A.V.; Ivanova, Y.A.; Rey, M.; Tashkun, S.A.; Toon, G.C.; Sung, K.; Tyuterev, Vl.G.
Highlights: PH3 line list at 296 K is theoretically modeled in the 2733–3660 cm −1 region. 5768 PH3 experimental line positions are reproduced with a 0.00185 cm −1 rms . 1752 PH3 experimental line intensities at 296 K are modeled with 10.9% rms. Abstract: Improved analysis of positions and intensities of phosphine spectral lines in the Octad region 2733–3660 cm −1 is reported. Some 5768 positions and 1752 intensities were modelled with RMS deviations of 0.00185 cm −1 and 10.9%, respectively. Based on an ab initio potential energy surface, the full Hamiltonian of phosphine nuclear motion was reduced to an effective Hamiltonian using high-order Contact Transformations method adapted to polyads of symmetric top AB3 -type molecules with a subsequent empirical optimization of parameters. More than 2000 new ro-vibrational lines were assigned that include transitions for all 13 vibrational Octad sublevels. This new fitting of measured positions and intensities considerably improved the accuracy of line parameters in the calculated database. A comparison of our results with experimental spectra of PNNL showed that the new set of line parameters from this work permits better simulation of observed cross-sections than the HITRAN2012 linelist. In the 2733–3660 cm −1 range, our integrated intensities show a good consistency with recent ab initio variational calculations.